Mechanical characterisation of interface shear strain of multi-layer composite pavement. Issue 9 (29th July 2021) - Xu, Yongli; Fan, Wei; Cheng, Peifeng; Shan, Liyan
ABSTRACT: As interface bonding is a weak part of multi-layer composite, it is necessary to take a research on interface bonding mode of asphalt pavement overlay on cement concrete structure, which include: common bonding, super bonding and stress absorbing layer (SAL) sandwich. The strain gage method was used to collect strain values to evaluate the strain distribution at each of the following four locations: the middle of the asphalt pavement layer, the interface between the asphalt pavement concrete at the mid-span, L/4 span and fulcrum. There is a difference on the quantitative analysis of the strain distribution of bonding modes at each location. It can be concluded that strong bonding controls the force and deformation concentrated at the interface. It is also favourable to reduce the shear force and prevents extension at the interface. The results can explain well the mechanical characteristics at the interface in different bonding modes and provide technical support for the selection of overlay mixture and bonding mode.